Término para citar en el juicio de alimetnos y el derecho de defensa del alimentante en el cantón Tulcán - Martínez Guamán, Gabriela Jacqueline (2017)
This research is necessary and of great importance due to the topic's relevance and social impact. In the processing of alimony claims, it is required from the filing of the claim, and the plaintiff is aware that the alimony trial cannot be declared unlawfully abandoned. Ecuadorian law requires a more complete, precise, and concise approach so that judges can suspend the determination of alimony until the alimony claimant is legally summoned, thus avoiding the accumulation of alimony payments and, at the same time, guaranteeing the speed of the process and the legitimate right of defense of the alimony payer.